Low preoperative plasma cholinesterase activity as a risk marker of postoperative delirium in elderly patients - Cerejeira, Joaquim; Batista, Pedro; Nogueira, Vasco; Firmino, Horácio; Vaz-Serra, Adriano; Mukaetova-Ladinska, Elizabeta B. (Age and ageing, 2011)
Background: delirium is a frequent neuropsychiatric syndrome affecting medical and surgical elderly patients. Cholinergic dysfunction has been implicated in delirium pathophysiology and plasmatic acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) activities are suppressed in patients with delirium. In this cohort study, we investigated whether these changes emerge during delirium or whether they are present before its onset. Methods: plasma activities of AChE and BuChE were measured pre- and postoperatively in consecutive patients ≥60 years old undergoing elective total hip replacement surgery. In addition to a comprehensive clinical and demographic baseline evaluation, venous blood samples were collected from each subject in the morning of hospital admission's day and in the morning of the first postoperative day. Delirium was screened daily with confusion assessment method (confirmed with diagnostic and statistical manual of mental disorders (DSM-IV)-TR). Results: preoperatively, plasma esterase activity was significantly lower in patients who developed delirium compared with the remaining subjects. Following surgery BuChE activity was lower in the delirium group but this difference disappeared after controlling for preoperative values. Plasma cholinesterase activity correlated positively with calcium and haemoglobin and negatively with total bilirubin and international normalised ratio. Conclusion: plasma cholinesterase activity can be a useful candidate biomarker to identify subjects at greater risk of developing postoperative delirium.